Practical software engineering : - Manassis, Enricos (Addison-Wesley, 2004)
Developers working on Microsoft technologies have been slower to adopt tried and true best practices from other platforms (e.g. object-oriented methodologies, full lifecycle approaches, etc.). The coming of the .NET platform has given cause for Microsoft-oriented developers to rethink their traditional philosophy. In this new book, Enricos Manassis takes the reader through a case study for specifying, analysing, designing, implementing, and testing a sample software system on the .NET platform. In so doing, the book presents the reader with an integrated vision of three dimensions in software development: process, techniques, and technology. The book contains a running case study that will help the practitioner examine the making of software from all angles, and the reader will emerge with a deeper understanding of how better software can be built.